Classroom and music teachers' perceptions about the development of imagination and creativity in primary music education - Sehnaz Sungurtekin (Journal of Pedagogical Research, 2021)
Despite the importance of musical creativity in combining existing musical knowledge in novel ways, research suggests that primary school teachers' practices do not adequately stimulate and develop children's musical creativity. In this regard, the purpose of this paper was to investigate teachers' perspectives on the development of imagination and creativity in primary music education. A phenomenological study approach was adopted to better understand how classroom and music teachers experience and ascribe meaning to imagination and creativity, as well as to assess the status of the two phenomena in primary music education. The results demonstrated that classroom and music teachers thought imagination and creativity were important for improving students' learning skills, underlining the importance of these phenomena in music education. Teachers linked product learning to student performances in playing their own instruments, creating rhythms with various materials, and writing poetry and lyrics. While a few music teachers emphasized the creation of melodies and rhythms, no emphasis on structural and intentional composing, and no product descriptions were provided. Teachers' thoughts on what adjustments need to be made within the primary music curriculum to equip students as imaginative and creative thinkers are also covered in this article following the introduction of a creative curriculum in primary music education.